2021
DOI: 10.1002/aic.17139
|View full text |Cite
|
Sign up to set email alerts
|

Coupling particle scale model and SuperDEM‐CFD for multiscale simulation of biomass pyrolysis in a packed bed pyrolyzer

Abstract: An efficient biomass pyrolysis process requires a comprehensive understanding of the chemical and physical phenomena that occur at multi‐length and time scales. In this study, a multiscale computational approach was developed and validated for biomass pyrolysis in a packed‐bed reactor by integrating pyrolysis kinetics, a particle scale model, and Superquadric Discrete Element Method‐Computational Fluid Dynamics (SuperDEM‐CFD) in open‐source code MFiX. A one‐dimensional particle–scale model that discretizes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…In the latter configuration, for the laminar flow regime of supercritical fluid, the influence of flow velocity, direction, and density gradient over heat transfer was analyzed. 219 Gao et al 220 developed a multiscale computational approach to study biomass pyrolysis in a packed bed reactor via coupled integration of the reaction kinetics, particle scale model, and super quadric DEM-CFD model using open source code MFiX. The single particle model and coupled model were compared with particle pyrolysis and packed bed experiments, and the models fairly reproduced the experimental results.…”
Section: Modeling Approaches To the Pyrolysismentioning
confidence: 99%
“…In the latter configuration, for the laminar flow regime of supercritical fluid, the influence of flow velocity, direction, and density gradient over heat transfer was analyzed. 219 Gao et al 220 developed a multiscale computational approach to study biomass pyrolysis in a packed bed reactor via coupled integration of the reaction kinetics, particle scale model, and super quadric DEM-CFD model using open source code MFiX. The single particle model and coupled model were compared with particle pyrolysis and packed bed experiments, and the models fairly reproduced the experimental results.…”
Section: Modeling Approaches To the Pyrolysismentioning
confidence: 99%
“…In the case of the one-pot approach, mesoscale and reactor-scale models are resolved simultaneously, yielding more realistic process simulation. Gao et al 155 developed a multiscale simulation framework by coupling a 1-D particle-scale model and a shape-resolved SuperDEM-CFD model for a lab-scale biomass pyrolyzer simulation. Later, Gao et al 153 applied the multiscale model for a pilot-scale biomass pyrolyzer by integrating detailed pyrolysis kinetics, a 1-D particle-scale model, and a multiphase particle in cell (MPPIC) reactor model (Figure 7).…”
Section: ■ Mesoscale Modeling Methodsmentioning
confidence: 99%
“…In the case of the one-pot approach, mesoscale and reactor-scale models are resolved simultaneously, yielding more realistic process simulation. Gao et al developed a multiscale simulation framework by coupling a 1-D particle-scale model and a shape-resolved SuperDEM-CFD model for a lab-scale biomass pyrolyzer simulation. Later, Gao et al .…”
Section: Mesoscale Modeling Methodsmentioning
confidence: 99%
“…Some studies [28] reported simulations by coupling a one-dimensional particle model with a reactor model for biomass pyrolysis. Gao et al [29] developed a multiscale model by integrating a simple biomass pyrolysis kinetics, a particlescale model, and a shape-resolved SuperDEM-CFD model [30,31] for biomass pyrolyzer simulation. However, a multiscale simulation by integrating a detailed kinetics mechanism, a particle-scale model, and a reactor model was seldom reported in the literature.…”
Section: Introductionmentioning
confidence: 99%